Ответ:
3.а) -16у б) -8
4. -19,8 = - 19,8
Пошаговое объяснение:
3. при х = -0,7 у = 0,5
а) 7(х - 2у) - 2(2х + у) - 3х = 7х - 14у - 4х - 2у - 3х = 0х - 16у = -16у
б) -16 * 0,5 = -8
<u>Проверим:</u>
7(х - 2у) - 2(2х + у) - 3х = 7*(-0,7 - 2*0,5) - 2(2*(-0,7) + 0,5) -3(-0,7) = 7*(-1,7) - 2(-0,9) + 2,1 = -11,9 + 1,8 + 2,1 = -11,9 + 3,9 = -8
4. 4 1/2(2х - 4) - 8,1(2/9 + 1 1/9х) = -19,8
4,5(2х - 4) - 81/10(2/9 + 10/9х) = -19,8
9х - 18 - 9/5 - 9х = -19,8
- 18 - 9/5 = - 19,8
-18 - 1,8 = - 19,8
-19,8 = - 19,8